Effect of learning orientation dimension on small medium enterprise performance - Abu Bakar, Hatinah; Mahmood, Rosli; Ismail, Nik Nor Hasimah (American Scientific Publishers, 2015)
This study aims to determine the association between learning orientation dimension namely commitment to learn, share vision, open mindedness and SME performance.According to the hypotheses formulated; there is significant relationship between commitment to learn, shared vision and open mindedness and SME performance.The sample were 368 managers/owners of SMEs.Questionnaires adopted from previous research were used to measure the learning orientation and firm performance. Smart SEM-PLS 3.0 were employed in this study. The findings revealed that the commitment to learn does not significantly influence the SME performance in SMEs.Meanwhile, shared vision and open mindedness significantly influence performance.